Trade unions and socio-labour actors in the context of austerity: from the voluntarism of protests to the fear of alliances - Costa, Hermes Augusto (2017)
Especially in the years of the troika’s intervention in Portugal, austerity policies have put pressure on union organizations (faced with tendencies to individualize labour relations and the need to safeguard vested rights), as well as other socio-labour actors (predisposed to denounce different modalities of precariousness in work and life). But if work and precariousness filled the discourses of one or another organization, the pragmatism of the answers proved foolhardy in building alliances between the two. As a corollary of this, two challenges are highlighted in the construction of a “trade-unionism of the precarious”, highlighting – in the form of institutional construction and social mobilization – the tensions and possibilities inherent in it.